SUSTAINABILITY ORIENTED INNOVATION ANALYSIS: LOW SULFUR MARINE FUEL OIL (LS MFO) TOWARDS INDONESIA'S GREEN PORT - Sari, Dian Inda; Nidar, Sulaeman Rahman (JURNAL DARMA AGUNG, 2024)
The Indonesian government has demonstrated its commitment to facilitating the transition towards zero-carbon fuel in maritime operations, along with the evolution of Indonesian ports into environmentally sustainable hubs. This commitment is exemplified through the initiation of low sulfur marine fuel oil (LS MFO) production, intended for naval armada fuel, within the port supply chain. This endeavor signifies a strategic move towards fostering greener practices within the maritime sector, aligning with global efforts to mitigate carbon emissions and promote sustainable development.